The Asian tiger mosquito, Aedes (Stegomyia) albopictus (Skuse), a vector of dengue, chikungunya and zika viruses, reaches Portugal (Diptera: Culicidae) - Marabuto, Eduardo; Rebelo, Maria Teresa (Zootaxa, 2018)
The Asian tiger mosquito, Aedes (Stegomyia) albopictus (Skuse), is a tropical species originally from south-eastern Asia (Hawley, 1988). It has experienced a rampant human-mediated range expansion since the 1970s to now occupy almost the whole of the tropical and subtropical areas of the world. As an eclectic haematophagous species, it attacks humans and is able to use a number of man-made and natural structures where stagnant water is present (Estrada-Franco & Craig, 1995). Eggs are able to survive for extended periods of time in complete dryness and diapause over unsuitable cold season, making it an especially resilient species (Hawley, 1988).